Association between FVL G1691A, FII G20210A, and MTHFR C677T and A1298C polymorphisms and Turkish women with recurrent pregnancy loss - Irem Yengel; Tulay Yorulmaz; Murat Api (Medicinski glasnik, 2019)
Aim: Recurrent pregnancy loss (RPL) poses a challenge in reproductive medicine because the etiology is often unknown. Here we investigated the frequency of mutations in the Factor V Leiden (FVL), prothrombin (FII), and methylene tetrahydrofolate reductase (MTHFR) genes in women with RPL and healthy women. Methods: Blood samples were obtained from patients with ?2 consecutive pregnancy losses and no identifiable etiology before 12 weeks of pregnancy (n=145). The control group comprised 105 age-matched women with ?2 live births. Results: The frequency of homozygotes for FVL 1691AA was 15 (10.3%) in patients and three (2.86%) in controls (p=0.073), while for FII 20210AA it was eight (5.5%) and one (0.9%), respectively (p=0.055). For two polymorphisms in MTHFR, genotype frequencies of 89 (61.4%) were found in patients and 55 (52.4%) in controls for 677TT (p=0.322), and 89 (61.4%) and 62 (59%) for 1298CC, respectively (p=0.810). Conclusion: Despite a trend towards significance for FII G20210A, no significant differences in genotype frequencies of these polymorphisms between patients and controls was found. No evidence of the role of FVL G1691A, MTHFR C677T, and MTHFR A1298C in RPL in our Turkish cohort was found; however, further investigation of FII as a culprit gene in RPL is warranted.
Keywords: gene polymorphisms; habitual abortions; MTHFR A1298C; MTHFR C677T polymorphisms; methylenetetrahydrofolate reductase; thrombophilia